(untitled) (Journal of Dhaka Medical College, 2024)
Introduction: Birth defects are one of the major cause of stillbirths and neonatal mortality in developed and developing countries. The prevalence of birth defects varies in different parts of the world. In many cases, the causes are unknown; however, several factors known to be associated are genetic factors, maternal age, health, dietary factors, maternal infections, geographical factors, drugs, smoking and irradiation. Objectives: To identify the pattern of birth defects, association and their outcomes among neonates Methodology: This observational cross-sectional study was conducted in the department of neonatology, Dhaka Medical College Hospital, Dhaka from 1st July 2019 to 30th June 2021. Sample was collected by purposive sampling technique. Total 407 babies were enrolled. Out of them 207 babies were with birth defects in group-A and 200 babies had no birth defects in group-B. Detail demographic data were collected from the informant and recorded in structured case report form. Clinical examination and relevant investigations were done. Data processing work consist of registration schedules, editing computerization, preparation of dummy table, analyzing and matching of data. Results: In this study the two study groups were almost similar with respect to their demographic characteristics like sex, residence, place of delivery, mode of delivery, gestational age, parity and maternal age. The total number of admission during this period was 3050 and total number of birth defects was 207 (6.78%0). In this study on evaluation of maternal risk factors, group-A maternal high blood pressure were in 25.12% cases( OR=1.62;p=.002), maternal diabetes were in 15.46% cases( OR=1.12;p=.001), poor maternal nutritional status was 14.50%( p=.001), history of taking folic acid was 9.66%(OR=0.10;p=.001), 5.80% of the patient had history of exposure to antenatal radiation(OR=.06;p=.001), 4.43% had history of consanguinity(OR=.05;p=.001), 2.420% of women noticed that exposure to pesticides(OR=.025;p=.001), H/O of taking anticonvulsant was 2.420%(OR=.025;p=.001). Group-B was maternal high blood pressure in 7.25% cases(OR=.078;p=.001), maternal diabetes were in 6.28% cases(OR=.067;p=.001), poor maternal nutritional status was 5.80%(p=.001), history of taking folic acid was 4.83% (OR=.051;p=.001), 1.45% of the patient had history of exposure to antenatal radiation(OR=.015;p=.001) and 0.97% had history of consanguinity(OR=.01;p=.001). In this study pattern of birth defects summarized as the cardiovascular system defects was the most commonly affected(26.57%), followed by defects in the head, neck ear,- and eye(19.32%), Syndromes(14.50%), gastrointestinal defects(12.56%), musculoskeletal system defects(10.14%), central nervous system defects (8.70%) and genitourinary system(4.83%) of total defects. In group-A 78.26% of the patients recovered and 23 patients expired during hospital stay (p=.001). In group-B 85.99% of the patients recovered and 17 patients expired. Conclusion: Congenital cardiac defects were the most prevalent anomaly detected. Maternal high blood pressure and diabetes are the risk factors of birth defects in neonates. Antenatal diagnosis and proper management can improve the outcome of these neonates. J Dhaka Med Coll. 2023; 32(1) : 43-50